Study of Making Gluten-Free Fettuccine from Taro Flour (Colocasia esculenta L. Schoot) - Sekti Rahardjo; Aminudin; Saleha; Tatik Sriwulandari; Nisa Rahmaniyah Utami (JURNAL AGROINDUSTRI HALAL, 2024)
We often encounter fettuccine pasta in cafes and restaurants, usually made from wheat flouras the main ingredient. Wheat flour is a food ingredient that contains gluten, which is a proteincompound from cereals that cause allergies and irritate the small intestine and can also causeceliac (autoimmune) disease in certain people. Several studies have substituted wheat flourfor making fettuccine with non-gluten taro flour. The formula obtained is still a mixture of taroflour and wheat flour. This research used 100% pure taro flour with additional ingredients oftwo types of egg yolk, namely chicken egg yolk and duck egg yolk. This research aimed todetermine the organoleptic results of fettuccine from 100% taro flour based on theformulation using the type of egg yolk and boiling time. This study used a completelyrandomized trial (CRD) design with four treatments and two repetitions. The types oftreatment in this study were the use of duck eggs with a boiling time of 35 seconds, the use ofboiled duck eggs for 1 minute, the use of boiled chicken eggs for 35 seconds, and the use ofboiled chicken eggs for 1 minute. The research results showed that fettuccine was successfullymade using 100% taro flour without being mixed with wheat, using additional egg yolk as abinder. A perfect assessment was obtained from the expert panelists for the duck egg yolkformula boiling for 1 minute. The type of egg yolk and boiling time affect the sample in termsof taste, color, and texture, but not aroma.